Circling the End of the Line in Monsoon: Glints of Significance Across Vimala Devi's Short Story Cycle - e Castro, Paul Melo (Archīum Ateneo, 2024)
This article analyzes Vimala Devi’s Monsooni (the 2019 English translation of her Monção, originally published in Portuguese in 1963, with a second augmented edition in 2003) as a short story cycle, a genre that differs as much from the traditional novel as from non-integrated collections of short narratives in its “tension between variety and unity, separateness and interconnectedness, fragmentation and continuity, openness and closure” (Lundén 12). It is this generic affiliation, the author argues, that makes possible Devi’s particular portrait of late-colonial Goa. Drawing on various theorizations of the short story cycle genre, the article scrutinizes the interconnections and breaks present across and between the fourteen short stories that comprise Monsoon and conclude that it is the oscillation between centripetal and centrifugal forces that enables the work’s representation of a polity sutured together along its divisions. Monsoon, proposing a new figure for the short story cycle, works like a gem in which the stone of context is cut to form a set of planes at angles to one another, and where each individual face constitutes a side of Goa’s pre-1961 social formation. The beauty of Devi’s narratives is that each aspect yields new glints of significance regarded in different lights. In each character there is a new metaphor for certain conditions of life in bygone Goa; the overall effect of these depictions of truncation and discontent is cumulative and mutually illuminating.